Nicholas II, the last Tsar - Paterson, Michael (London : Robinson, 2017)
The character of the last Tsar, Nicholas II (1868-1918) is crucial to understanding the overthrow of tsarist Russia, the most significant event in Russian history. Nicholas became Tsar at the age of 26. Though a conscientious man who was passionate in his devotion to his country, he was weak, sentimental, dogmatic and indecisive. Ironically he could have made an effective constitutional monarch, but these flaws rendered him fatally unsuited to be the sole ruler of a nation that was in the throes of painful modernisation. That he failed is not surprising, for many abler monarchs could not have succeeded. Rather to be wondered at is that he managed, for 23 years, to hold on to power despite the overwhelming force of circumstances.
englanti
Luett. M. Puominen
KIRJA / BOK
Keywords: Nikolai II, -- Venäjän keisari; henkilöhistoria; keisarit; hallitsijat; historia; Venäjä; elämäkerrat; elämäkerrat